Impacts of early decision making on the control of COVID-19 pandemic (Research, Society and Development, 2020)
This paper aims to analyze the impacts of early decision making in the context of uncertainty caused by COVID-19 in the Brazilian federal states of Ceará (CE) and Rio Grande do Norte (RN). Results were analyzed through the lens of bounded rationality. Research methodology followed four steps (i) content analysis of state government documents; (ii) presentation of data from the pandemic in both states; (iii) building a timeline and, (iv) comparative analysis. Main results indicate that decision making regarding containment measures happened in distinct moments of the epidemic crisis in both states and with different rigor, resulting in a more severe situation in the state of CE than RN. The paper contributes to the literature in public management as results show that an early decision making amidst an uncertain scenario provided greater control of the epidemic curve.